Afrahat Mowa XVI – O narodach, które zastąpiły naród - Uciecha, Andrzej (Vox Patrum, 2019)
The homily On the Peoples in Place of the People is the 16th in order of the collection of Aphrahat’s Demonstrations. The Persian sage clearly addresses the theme of „Israel” and „the nations”. Aphrahat demonstrates the divine „vocation of the nations” and „the rejection of Israel”. A polemical message in On the Peoples in Place of the People seems not to have considered that Israel itself was „the nation from the nations”. The people Israel was rejected and the peoples of gentiles took their place. Israelites were wearned over and over by the prophets, but in vain, so God abandoned tchem and replaces with „the peoples” of the new covenant. The vocation of the peoples was prior to that of the people of Israel. By means of the gentiles God provoked Israel.